1999
DOI: 10.1128/iai.67.1.417-420.1999
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Soluble CD14 in Sera of Periodontitis Patients

Abstract: Soluble CD14 (sCD14) mediates the response to lipopolysaccharide (LPS) in cells lacking membrane-bound CD14. We determined sCD14 concentrations in the sera of 38 periodontitis patients and 25 healthy controls by enzyme-linked immunosorbent assay. The sCD14 levels in the sera of patients with periodontitis were significantly higher than those of healthy subjects and decreased after treatment. Enhanced levels of sCD14 in serum may contribute to the host response to LPS in periodontitis. Furthermore, we showed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 35 publications
(37 reference statements)
6
39
0
1
Order By: Relevance
“…Increased levels of soluble CD14 were found in the serum of patients with periodontitis compared with individuals without periodontitis. 26 Thus, in the setting of periodontitis, CD14 in the systemic circulation as well as upregulated expression of Cd14 by b cells may both be evident.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of soluble CD14 were found in the serum of patients with periodontitis compared with individuals without periodontitis. 26 Thus, in the setting of periodontitis, CD14 in the systemic circulation as well as upregulated expression of Cd14 by b cells may both be evident.…”
Section: Discussionmentioning
confidence: 99%
“…In general, increased levels of sCD14 have been found in non-infectious and infectious diseases such as systemic lupus erythematosus (Nockher et al, 1994), rheumatoid arthritis (Horneff et al, 1993), polytraumatised and severely burned patients (Kruger et al, 1991), septic shock (Landmann et al, 1995), malaria (Wenisch et al, 1996), brucellosis (Ayaslioglu et al, 2005), HIV-infection (Lien et al, 1998), and tuberculosis with or without HIV infection (Lawn et al, 2000). Hayashi et al (1999) investigated the concentrations of sCD14 in the sera of patients with adult periodontitis, early-onset periodontitis and compared with periodontally healthy donors. They found that sCD14 concentration in serum was significantly higher in patients with periodontitis than in healthy controls, but did not find significant difference between both clinical forms of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The CD14 −260 SNP has previously been associated of increased risk with myocardial infarction (Hubacek et al 1999) and Crohn's disease (Klein et al 2002). Furthermore, increased serum levels of sCD14 have been associated with periodontitis (Hayashi et al 1999).…”
Section: Modifying Disease Genes In Relation To Periodontitismentioning
confidence: 99%